Efektivitas Media Video Animasi Motion Graphic pada Mata Pelajaran Bahasa Inggris Terhadap Hasil Belajar Siswa Kelas VII SMP Negeri 39 Padang (Indo-MathEdu Intellectuals Journal, 2024)
Lack of desire and low student participation in monotonous Englisgh learning can lead to low student learning outcomes. So support is needed in the form of media to overcome this problem. This study aims to determine the effectiveness of motion graphic animation video media in Englisgh subjects on the learning outcomes of grade VII students of SMP Negeri 39 Padang. The type of research is in the form of quantitative research with experimental methods. The sample in this study is 60 students consisting of an experimental class and a control class. Data analysis technique uses a t-test to determine student learning outcomes in English subjects. The results showed that there was a difference in the learning outcomes of the experimental class with an average of 73.83 and the control class with an average of 67.33. The use of motion graphic animation video media is effective in Englisgh subjects on the learning outcomes of grade VII students. It can be concluded that the learning outcomes of students who use motion graphic animation video media in Englisgh subjects have a significant impact on student learning outcomes